Genome Survey and SSR Analysis of Camellia nitidissima Chi (Theaceae) - Yu Bai; Lin Ye; Kang Yang; Hui Wang (Genetics Research)
Camellia nitidissima Chi (CNC), a species of golden Camellia, is well known as “the queen of camellias.” It is an ornamental, medicinal, and edible plant grown in China. In this study, we conducted a genome survey sequencing analysis and simple sequence repeat (SSR) identification of CNC using the Illumina sequencing platform. The 21-mer analysis predicted its genome size to be 2,778.82 Mb, with heterozygosity and repetition rates of 1.42% and 65.27%, respectively. The CNC genome sequences were assembled into 9,399,197 scaffolds, covering ∼2,910 Mb and an N50 of 869 base pair. Its genomic characteristics were found to be similar to those of Camellia oleifera. In addition, 1,940,616 SSRs were identified from the genome data, including mono-(61.85%), di-(28.71%), tri-(6.51%), tetra-(1.85%), penta-(0.57%), and hexanucleotide motifs (0.51%). We believe these data will provide a useful foundation for the development of novel molecular markers for CNC as well as for further whole-genome sequencing of CNC.